A A Study on the Division of Space Functions Based on Social Levels in Sasak Traditional Settlements Sade – Central of Lombok - Saptaningtyas, Rini Srikus (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
One of the traditional settlements on the island of Lombok is in the Sade Hamlet - Central Lombok. This hamlet is one of the hamlets that is unique in residential buildings and is interesting to discuss. The purpose of this study was to examine the differences in the shape of the bale plan based on local socio-cultural strata. The research method used is a qualitative approach. The data collection technique used in this study was a survey. The field observations were carried out to obtain direct data on the existing physical conditions. In addition, interviews were conducted with the informants (residents of Sade hamlet) to find data that had not been revealed in the field. The data analysis technique in this research is descriptive analysis. This study concludes that the social level in traditional use dramatically determines the typology of the building. Bale Tani and Bale Bontar lie in the building foundation, where Bale Bontar is a higher foundation than Bale Tani, and there are differences in the division of space functions in Bale Tani and Bale Bontar.